APPRAISAL ATTITUDE ON EDITORIAL NEWS: OUR DISASTROUS PRESIDENT - Susanto, Dias Andris; Bimo, Djoko Sri (LPPM Institut Pendidikan Nusantara Global, 2023)
Appraisal Theory's linguistic discourse analysis gives different techniques to analyze